SUKAPTINAH AND HAJINAH’S ROLES IN THE NATIONALIST MOVEMENT IN INDONESIA - Amini, Mutiah (Balai Pelestarian Kebudayaan Wilayah X, 2017)
In the history of the Indonesian women’s movement, Siti Sukaptinah Sunaryo Mangunpuspito (hereinafter referred to as Sukaptinah, 1907-1991) and Siti Hajinah Mawardi (hereinafter referred to as Hajinah, 1906-1995) were known as activists in women’s organizations during the colonial period. Sukaptinah was a member of an Islamic nationalist group (JIBDA – Jong Islaminten Bond Dames Afdeling) with a background on the Indonesian education movement, Taman Siswa. She was also active in the first Indonesian Women’s Congress of 1928. Hajinah who came from Aisyiah (the women’s wing of the large modernist Islamic organization, Muhammadiyah) was known as one of the members of the Indonesian Women Congress. In addition to their activities in the Indonesian women’s movement and the Islamic movement, they also played roles in national movement, a matter which is not quite recognized. Hajinah did not only act as the head of Aisjiah, but also partook actively in press through Soeara ‘Aisjiah magazine (Aisjiah’s quarterly magazine) and Isteri (magazine existing in embryo in the first women congress). An activist of Aisjiah, she gave meaning of the independence achievement through the domain of family (social). On the other hand, Sukaptinah, activist of Jong Islaminten Bond, who also actively participated in the first, second, third and fourth Indonesian Women Congress, gave meaning of the national movement through political domain. She had sat in the parliament as the woman representative in the government council in Semarang, with the most important political thought in the form of the importance of woman to struggle their rights to vote and be voted in the parliament.Di dalam sejarah gerakan perempuan, Siti Sukaptinah Sunaryo Mangunpuspito (yang selanjutnya disebut Sukaptinah, 1907-1991) dan Siti Hajinah Mawardi (yang selanjutnya disebut Hajinah, 1906-1995) dikenal sebagai aktivis organisasi perempuan pada masa kolonial. Sukaptinah adalah anggota kelompok nasionalis Islam (JIBDA – Jong Islaminten Bond Dames Afdeling) dengan latar belakang pendidikan nasionalis, Taman Siswa. Sukaptinah juga aktif di dalam Konggres perempuan Indonesia Pertama pada 1928. Sementara itu, Hajinah merupakan anggota Aisjiah (sayap perempuan dari salah satu organisasi modernis Islam, Muhammadiyah) serta dikenal sebagai salah seorang anggota Konggres Perempuan. Selain aktivitasnya di dalam gerakan perempuan Indonesia dan gerakan Islam, mereka juga berperan penting di dalam gerakan nasional, yang selama ini jarang diperbincangkan. Hajinah tidak hanya pernah menjadi salah seorang pimpinan Aisjiah, tetapi juga menjadi pemikir penting atas terbitnya majalah Soeara ‘Aisjiah (majalah terbitan rutin Aisjiah) dan Isteri (majalah yang memiliki keterkaitan erat dengan Konggres Perempuan Pertama). Sebagai aktivis Aisjiah, Hajinah berperan dalam pemberian arti kebebasan berpendapat melalui ruang keluarga (sosial). Selain itu, Sukaptinah, merupakan aktivis Jong Islaminten Bond, yang juga berpartisipasi aktif di dalam Konggres Perempuan Pertama, Kedua, ketiga, dan Keempat, dengan memberikan arti yang penting melalui ranah politik. Sukaptinah juga pernah duduk di parlemen di Semarang sebagai wakil perempuan, dengan pemikiran politiknya tentang pentingnya perempuan secara tegas memperjuangkan hak pilih dan keterwakilan perempuan di parlemen.